Efficacy of subcutaneous doses and a new oral amorphous solid dispersion formulation of flubendazole on male jirds (Meriones unguiculatus) infected with the filarial nematode Brugia pahangi. - Chelsea Fischer; Iosune Ibiricu Urriza; Christina A Bulman; K C Lim; Jiri Gut; Sophie Lachau-Durand; Marc Engelen; Ludo Quirynen; Fetene Tekle; Benny Baeten; Brenda Beerntsen; Sara Lustigman; et al. (Public Library of Science (PLoS), 2019)
River blindness and lymphatic filariasis are two filarial diseases that globally affect millions of people mostly in impoverished countries. Current mass drug administration programs rely on drugs that primarily target the microfilariae, which are released from adult female worms. The female worms can live for several years, releasing millions of microfilariae throughout the course of infection. Thus, to stop transmission of infection and shorten the time to elimination of these diseases, a safe and effective drug that kills the adult stage is needed. The benzimidazole anthelmintic flubendazole (FBZ) is 100% efficacious as a macrofilaricide in experimental filarial rodent models but it must be administered subcutaneously (SC) due to its low oral bioavailability. Studies were undertaken to assess the efficacy of a new oral amorphous solid dispersion (ASD) formulation of FBZ on Brugia pahangi infected jirds (Meriones unguiculatus) and compare it to a single or multiple doses of FBZ given subcutaneously. Results showed that worm burden was not significantly decreased in animals given oral doses of ASD FBZ (0.2-15 mg/kg). Regardless, doses as low as 1.5 mg/kg caused extensive ultrastructural damage to developing embryos and microfilariae (mf). SC injections of FBZ in suspension (10 mg/kg) given for 5 days however, eliminated all worms in all animals, and a single SC injection reduced worm burden by 63% compared to the control group. In summary, oral doses of ASD formulated FBZ did not significantly reduce total worm burden but longer treatments, extended takedown times or a second dosing regimen, may decrease female fecundity and the number of mf shed by female worms.